2022
DOI: 10.3390/nu14102024
|View full text |Cite
|
Sign up to set email alerts
|

The SNP rs516946 Interacted in the Association of MetS with Dietary Iron among Chinese Males but Not Females

Abstract: This study aimed to explore the role of the single nucleotide polymorphism (SNP) rs516946 of the Ankyrin 1 (ANK1) gene in the relationship between dietary iron and metabolic syndrome (MetS) in the Chinese population. A total of 2766 Chinese adults (1284 males and 1482 females) were recruited. A 3-day 24-h dietary recall and weighing of household condiments were used to assess dietary intake. Anthropometric and laboratory measurements were obtained. After adjusting for age, region, years of education, intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A study on the relationship between ACE2 variants and left ventricular hypertrophy revealed that the minor alleles of ACE2 , rs2074192, and rs2106809, increased susceptibility to left ventricular hypertrophy in women, but not in men 21 . Another study explored the role of ANK1 SNP rs516946 in the relationship between dietary iron level and MetS, finding an interaction with the association between MetS and dietary iron in Chinese males, but not in females 22 . One possible reason for the sex-specific difference in our results is that ACE2 is located on the X chromosome, so the number of alleles varies significantly between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the relationship between ACE2 variants and left ventricular hypertrophy revealed that the minor alleles of ACE2 , rs2074192, and rs2106809, increased susceptibility to left ventricular hypertrophy in women, but not in men 21 . Another study explored the role of ANK1 SNP rs516946 in the relationship between dietary iron level and MetS, finding an interaction with the association between MetS and dietary iron in Chinese males, but not in females 22 . One possible reason for the sex-specific difference in our results is that ACE2 is located on the X chromosome, so the number of alleles varies significantly between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on the Shanghai Diet and Health Survey (SDHS), which was conducted from 2012 to 2013; the participants were followed up in 2019. It was a crosssectional study, and the methodology of this study has been described previously [17]. Briefly, a multi-stage stratified cluster random sampling was used to select participants from 54 communities across Shanghai from 2012 to 2013 (Figure 1).…”
Section: Study Participantsmentioning
confidence: 99%